Spatial parcellations, spectral filtering and connectivity measures in fMRI optimizing for discrimination - Duff, E; Sala, R (University of Oxford, 2018)
The dataset includes 15 subjects x 5 steady state conditions. Connectivity data has been computed using FSLNETS with the following options: - Timeseries from a set of 33 ROIs derived from functional data (Study-ROIs). - Correlation as dependency measures. - No bandpass filtering.